211k views
0 votes
1) Differentiate the following using the product rule or the quotient rule..

(i) y=(x^2 - 1)(x^3 + 3)

(ii) y=x^5 (3x^2+ 4x-7)

User Mun
by
5.8k points

2 Answers

5 votes
Refer to the photo attached.
1) Differentiate the following using the product rule or the quotient rule.. (i) y-example-1
User Adamarla
by
6.4k points
7 votes

Answer:

Explanation:

1) y=(x^2 - 1)(x^3 + 3)

From the product rule with u = x^2 - 1 and v = x^3, we find


(d)/(dx) {(x^2-1)(x^3+3)=(x^2-1)(d)/(dx) (x^3+3)+(x^3+3)(d)/(dx) (x^2-1)\\


(x^2-1)(3x^2)+(x^3+3)(2x)


=3x^4-3x^2+2x^4+6x\\=5x^4-3x^2+6x

2) y=x^5 (3x^2+ 4x-7)

--->
21x^6+24x^5-35x^4

User Pierrotlefou
by
6.8k points